Long-term effects of a primary school-based overweight preventive intervention on physical fitness and physical activity: a propensity score-matched retrospective cohort study within the Generation R Study - Hein Raat; Liesbeth Duijts; Trudy Voortman; Daan Nieboer; Wilma Jansen; Michel Sebastiaan Smit; Famke Mölenberg; Rosalie Mensink-Bout (BMJ Open)
Objectives In this study, we evaluate the long-term effects (±1.5 years postintervention) of 6-year exposure to the Lekker Fit! intervention on physical fitness and physical activity (PA).Design The retrospective intervention evaluation is embedded within the Generation R Study in Rotterdam, the Netherlands, a population-based prospective birth cohort study.Setting Measurements took place in the research centre of the Generation R cohort study.Participants 5489 adolescents from the Generation R Study were eligible for inclusion within this study. Successful linking to school career data was possible for 4129 adolescents who were then retrospectively subdivided into a Lekker Fit! group, mixed group and regular school group based on their primary school career.Interventions The Lekker Fit! intervention is a multicomponent primary school-based intervention for the prevention of overweight. It focuses on a healthy diet and healthy lifestyle rather than focusing directly on the reduction of overweight. The intervention targets individual behaviour of children as well as their obesogenic environment and parental engagement in shaping their children’s behaviour.Primary and secondary outcome measures Aged 13/14 years old, physical fitness was measured with an incremental ergometer test. The actual highest achieved work rate was divided by the expected highest achieved work rate (age- and sex-related Dutch population-based reference data), and converted into z-scores. PA was determined by the number of days with at least 1 hour of PA, obtained by a self-reported questionnaire. Propensity score matching was performed to correct for non-random selection bias. Linear regression analyses were performed to estimate intervention effects.Results Children from the Lekker Fit! group had significantly lower fitness z-scores (−0.18 (95% CI −0.29 to –0.06), n=1826) compared with children from the matched regular school group. No Lekker Fit! intervention effect was found on PA (−0.12 (95% CI −0.36 to 0.12), n=1258).Conclusions No evidence was found for long-term favourable effects of a school-based multicomponent intervention on physical fitness and PA. Recommendations for policy and future research are discussed.